The Stress-Strength Model: R=P(Y < X) Gamma Case by Mathematica - Ehtesham Hussain; Muhammad Ahsanuddin (European Scientific Journal, ESJ, 2019)
In this paper, we considered the estimation of R=P(Y<X), dubbed asStress-Strength Model (SSM), in a framework of gamma distribution withunknown scale and shape parameters. This is not an easy computing problemin conventional mathematics. For such problems, a very important option isusing a Mathematica software, which has been employed to obtain solutionsto this problem.